CCNA 200-301. Official cert guide. Volume 2 - Odom, Wendell; Gooley, Jason; Hucaby, David (Cisco Press, 2025)
"CCNA 200-301 Official Cert Guide, Volume 2 from Cisco Press enables you to succeed on the Cisco exam the first time and is the only self-study resource approved by Cisco. Best-selling author Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills"--